Optic perineuritis - Mayuresh Naik; Sukriti Gupta; Prabhpreet Sethi; RamKrishan Duvesh; Harinder Singh Sethi; Harminder K Rai (BMJ Open Ophthalmology, 2021)
Optic perineuritis (OPN) is a rare inflammatory disorder in which the inflammation is confined to optic nerve sheath. It can be idiopathic or secondary to underlying systemic autoimmune disorder. It usually presents with unilateral progressive diminution of vision with pain on eye movements and optic disc oedema. Hence, clinically OPN mimics optic neuritis resulting in delayed diagnosis and suboptimal treatment. In contrast to optic neuritis, patients with OPN are usually of older age group and more likely show sparing of central vision. MRI is an important tool for diagnosis of OPN apart from optic nerve sheath biopsy. Perineural enhancement on MRI is diagnostic of OPN. Oral corticosteroid therapy gives dramatic and rapid improvement in signs and symptoms. Rapid tapering of steroids increases the risk of relapse. Overall, prognosis of OPN is generally good if adequate treatment is given timely.